Aesthetic Progression in Literary Translation - Jiang, Qiuxia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThe exploration of aesthetic progression in literary translation is a new area yet to be developed. Considering the fact that cognitive linguistic theories have not been fully exploited in literary translation, the present study proposes an image-based translation model out of the assumption that literary comprehension in translation involves not only cognitive activities such as identification of distinctive features and their distribution, but also the aesthetic experience; and successful production in translation does not rise from correspondence finding of individual words or sentences, but is procured by means of a mentally formulated image gestalt, an integrated entity of both linguistic organization and visualized scene.